浅析印尼小学汉字线上教学 ——以光明学校与信望爱学校为例 A BRIEF ANALYSIS OF INDONESIA PRIMARY SCHOOLS CHINESE CHARACTERS ONLINE TEACHING (Study Cases at Guang Ming and Ipeka School) - Melissa Octavia; Shihping Chan; Symphony Akelba Christian (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
摘要在汉语的学习过程中，汉字无疑成为学生的难题之一，同时也成为汉语教师在教学中的挑战之一。印尼至2020年3月中旬全国开始线上课，学校如何进行线上汉字课便是本研究的研究重点。本研究主要通过课堂观察与教师访谈对光明学校与信望爱学校进行研究。目的是为了更深入了解光明学校与信望爱学校疫情期间的线上汉字教学的情况。通过研究得知，无论在识字教学还是写字教学，教师大部分都使用PPT教学生识字和写汉字的笔顺笔画。教师会把汉字的字形跟图片或者GIF汉字笔顺放在PPT上展示给学生看。教师也会使用一些教学网站给学生设计识字练习。在汉字练习方面，教师最常使用的汉字练习方式是让学生在练习册上描汉字或者写汉字。 关键词：线上汉字教学；印尼；小学 AbstractIn the process of learning Chinese, Chinese characters undoubtedly become one of the difficult problems for students, and also one of the challenges for Chinese teachers in teaching. This study focused on Guang Ming School and IPEKA School through classroom observation and teacher interviews. The aim was to gain a deeper understanding of the online Chinese character pedagogy during the outbreak in the two schools. Through research, it is learned that in both literacy teaching and writing teaching, teachers mostly use PPT to teach students to read and write the strokes of Chinese characters. Teachers will put the glyphs and pictures or GIF Strokes with Chinese characters on the PPT and show them to the students. Teachers also use some teaching websites to design literacy exercises for students. In terms of Chinese character practice, the most commonly used Chinese character practice method by teachers is for students to draw or write Chinese characters on the exercise books.Keywords: Online Chinese characters teaching; Indonesia; Primary School